Digital consumer management: understanding and managing consumer engagement in the digital environment - Mogaji Emmanuel (London and New Yark Routledge, 2024)
Integrating consumer behavior, digital marketing, digital platform management, web analytics, and marketing insights, Digital Consumer Management provides a holistic understanding$1 (Bfrom a brand perspective$1 (Bof the management of consumers and consumption in the digital ecosystem.s
Keywords: Consumer Behavior; Marketing; Internet/ Digital Marketing/ e- marketing